Diene containing polymer brushes for bioimmobilization - Üzüm, Yasemin Nursel. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Reactive polymer brushes have emerged as an active area of research in recent years. The increasing popularity of polymer brushes is due to the multiple advantages that they offer. In fact, they can be obtained with straightforward technical synthesis and they are suitable to a large range of functionalizable molecules. Compared to the polymers coated on a substrate with spin-coating technique, they are very resistant to harsh chemical environment. Surface-initiated atom transfer radical polymerization (ATRP) is commonly utilized since it provides good control of the polymer brush composition and thickness. Over the past decade, efficient chemical transformations based on various “click” reactions have been employed for functionalization of polymeric brushes. To date, all approaches require additional reagents and/or catalysts to achieve attachment of desired molecules. This thesis reports the first example of utilization of a Diels-Alder reaction based on functionalization strategy that allows efficient conjugation of polymer brushes under mild and reagent-free conditions. Polymer chains incorporating furan groups as side chains are “grafted from” silicon surfaces. These pendant furan moities react with a maleimide functionalized molecule of interest through the Diels-Alder reaction. The specificity of the functionalization is gained by the presence of the antibiofouling polyethylene glycol methyl ether methacrylate monomer. Copolymers with varying amounts of furfuryl methacrylate, were synthesized in this study. The reactivities of these furan containing brushes were investigated through the immobilization of maleimide functionalized molecules, such as the model compound N-ethylmaleimide, a fluorescent dye BODIPY-maleimide and biotin-maleimide ligand which enables the immobilization of Quantum-Dot streptavidin conjugates. Additionally, the reversibility of these conjugations is demonstrated by taking advantage of the reversible nature of the Diels-Alder reaction.
Keywords: Reactive polymers.